Perancangan Injection Blowing Tools dengan Line Slider untuk Mesin Blow Molding dengan Kapasitas Volume 300 Ml - Ikhsan, Subkhan Nur; Budiyantoro, Cahyo; Suwanda, Totok; Nugroho, Adi (JMPM : Jurnal Material dan Proses Manufaktur, 2018)
Blow molding machine is a machine that used to produced plastic bottle with injection air system to blowing the soft preform (±100℃)  at 7 bar pressure of air. They are two main components in injection blowing tools i.e, injection tools to distribute the high pressure air from compressor to the bottle preform and the line sliders to make a mold cavity can moving when the injection process ongoing and finished. To build the injection blowing tools, they are several main material that use, on the line sliders use the main material of low carbon steel type A36 ( 0,25% - 0,29% C) with strip and plate with force of 360 Ksi ( 250 MPa ), and the injection tools use the main material of Aluminium-alloy 4032 (Al, Si 12,5%, Mg, Cu, Ni) because it easy to make an model or profil with reasonable price. The main material on the shafts holder injector and blow pin use stainless steel 304 with max force of 515 MPa. The process to joint between the components are applying the welding model with fillet type and average on high of the neck weld 3 mm and use electrodes of RD-260 which E6013 electrode class with maximum strength 60 Ksi and use the bolt and nuts which average from material of SS 304 with size M6 - M16. In  the process injection, the ratio of large development due to the process injection ( BUR ) is 4 with the size of a bottle preform long 99 mm thick 2 mm and diameter 26 mm.